Covid Vaccine – A Promising Light - Rao, Bhagya Venkanna (Indian Journal of Pharmacy Practice)
We all had one simple question this year, is there a vaccine for COVID-19? Yes, finally, there is good news for all of us. Multiple vaccine candidates have shown promising preliminary data in large studies as safe and effective and are due to go for regulatory approval. One of them has been approved and already in use in several countries overseas. Here too, the National regulatory authority is currently reviewing many COVID-19 vaccines and soon we should be able to start administering them.